2008
DOI: 10.1038/sj.bjc.6604690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of G/A polymorphism, rs266882, in the androgen response element 1 of the PSA gene on prostate cancer risk, survival and circulating PSA levels

Abstract: Prostate-specific antigen (PSA) is a protease produced in the prostate that cleaves insulin-like growth factor binding protein-3 and other proteins. Production is mediated by the androgen receptor (AR) binding to the androgen response elements (ARE) in the promoter region of the PSA gene. Studies of a single nucleotide polymorphism (PSA À158 G/A, rs266882) in ARE1 of the PSA gene have been conflicting for risk of prostate cancer and effect on plasma PSA levels. In this nested case -control analysis of 500 whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…A significant relationship was observed between the GG genotype and BPH (P = 0.033). In the studies by Salinas et al (2005) and Jesser et al (2008), no significant difference was found in the PSA-158 G/A polymorphism for prostate cancer. However, in a meta-analysis including 12 trials, the PSA-158 G/A polymorphism had no effect on prostate cancer risk.…”
Section: Discussionmentioning
confidence: 88%
“…A significant relationship was observed between the GG genotype and BPH (P = 0.033). In the studies by Salinas et al (2005) and Jesser et al (2008), no significant difference was found in the PSA-158 G/A polymorphism for prostate cancer. However, in a meta-analysis including 12 trials, the PSA-158 G/A polymorphism had no effect on prostate cancer risk.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, PSA is an IGFBP-3 protease. It cleaves IGFBP-3 [7,25], what results in an increase of free IGF-1 fraction in circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the promoter ARE-I region at the -158 position from starting point of transcription, onenucleotide polymorphism (A/G) was determined. It has been reported, this polymorphism is associated with higher PSA level and higher risk of PCa development [6,7,8].…”
mentioning
confidence: 90%
“…Some have reported an association with the same allele as the original study (Gsur et al , 2002 ;Medeiros et al , 2002 ;Cicek et al , 2005 ;Lai et al , 2007 ), while others have reported either a significant association in the opposite direction (Chiang et al , 2004 ;Binnie et al , 2005 ) or no association for this SNP (Wang et al , 2003 ;Salinas et al , 2005 ;Mononen et al , 2006 ;Severi et al , 2006 ;Cunningham et al , 2007 ;Pal et al , 2007 ;Penney et al , 2011 ). A meta-analysis of all studies published up until 2008 reported no evidence of association with prostate cancer risk overall (Supplementary Table 1; Jesser et al , 2008 ).…”
Section: Pre-gwas Klk Candidate Gene-association Studiesmentioning
confidence: 97%